Tax Morale and Fiscal Policy - Benno Torgler; Christoph A. Schaltegger (Center for Research in Economics, Management and the Arts (CREMA), 2005)
ax morale has received a growing attention in academics as well as in public life. The relevance of tax morale for fiscal policy cannot be neglected as tax morale can help to explain the level of tax compliance or tax evasion. This paper gives an overview of tax morale with a special focus on Switzerland. We highlight the magnitude and the de-terminants of tax morale that have been isolated so far and discuss directions for future research in this area. In particular, we concentrate on fiscal policy implications.
Keywords: H26; 330; tax morale; tax compliance; tax evasion; fiscal policy